Terrains of Country: Mapping Co-Design Methods - Nichols, Julie; Thomas, Uncle Lindsay; Thomas, Travis; Thomas, Jared; Tang, Fu Hong; Weber, Delene (UI Scholars Hub, 2024)
This paper explores the ‘discursive’ as well as the physical terrains of Country as part of a co-design methodology employed with Nukunu. It examines a curatorial and archival perspective in its documenting of Nukunu Country forming part of the Time Layered Culture Map (TLCMap) digital humanities infrastructure project. A literature review from Aboriginal and non-Aboriginal scholars presents perspectives around decolonizing Western ontological and epistemological structures as a mode of disrupting current, entrenched codification of knowledge. This paper seeks primarily to explore the Indigenization of information shared and re-presented in the co-design exercises of designing on Country to contribute to the preservation of Traditional Knowledge, in addition to designing facilities to house community whilst undertaking these practices. The methods include exploration of scholarly literature of co-design and architectural ethnographic practices, through a lens of recounting first-hand, in-the-field experiences that range from observational to direct engagement in cultural burning and camping on site to further understand and connect with all that constitutes Country. This study highlights the importance of observation and participation in architectural ethnographic methods, which positively strengthen the co-design process and support the preservation of cultural burning practices. It shows how the process reveals the cultural and ecological wisdom of the traditional community, contributing to the knowledge of Indigenous land management techniques.